Application of MIL-100(Fe) in drug delivery and biomedicine - Quijia, Christian Rafael [UNESP] (2021)
Metal-organic frameworks (MOFs) are an interesting and advantageous class of coordination polymers, constructed from metal ion/clusters and organic linkers. They have attracted growing research interest over the past decades and captured attention in the field of biomedical applications due to their high drug loading capacity, post-synthetic modification, and the ability to synthesize at the nanoscale size. In particular, MIL-100(Fe) is a mesoporous, environmentally friendly, and water-stable material. This review summarizes and discusses the recent advances in the synthesis of the micro and nano-MIL-100(Fe), the physicochemical stability concerning changes in pH, temperature, and physiological conditions, as well as biomedical applications such as biosensors, phototherapy, encapsulation methods, and drug release. Finally, future challenges and perspectives in this field are presented.